Pengaruh Partisipasi Anggaran Terhadap Kinerja Manajerial Pada Kantor Pos Di Bandar Lampung - Puspita, Indah Lia; Nopiyanti, Devi (Universitas Malahayati, 2024)
The purpose of this study was to determine how management performance at the Bandar Lampung Post Office is influenced by budget participation. The research sample consisted of 30 people. The data collection method used was a questionnaire. Statistical analysis using SPSS for Windows. The results showed that management performance was positively and significantly influenced by the Budget Participation variable. The impact of the budget participation variable (X1) on managerial performance is influenced by other factors outside this regression equation or other variables that are not evaluated, according to the results of the determination coefficient test (Adjusted R-Square).